Estratégia empresarial e vantagem competitiva na produção de cafés especiais - Giacchetta, Jerônimo (2011)
A company engaged in special coffee production was evaluated regarding the main aspects of the strategic business management in order to obtain competitive advantage in the specialty coffee market. The research was conducted at Fazenda Ponto Alegre, in the rural area of the city of Cabo Verde, Coelhos district, state of Minas Gerais, Brazil. A semi-structured interview was carried out when the interviewees were instructed by two questionnaires with a basic guide. One of the questionnaires asked about the work methods and business management at the time when the farm used to produce commodity-type coffees before 1992; the other approached the present situation of the company in the specialty coffee production. Based on the questionnaires, a comparative analysis of the two approaches was made to verify the business advantages and disadvantages. According to information gathered through questionnaires and extraction models of the five competitive forces, the Fazenda Ponto Alegre used sound business strategies to position themselves ahead of the competition in the special coffee market, reaching the goal of getting competitive advantage in business, such as reputation, brand, top quality product, and customer value. The Ponto Alegre farm is recognized by the specialty coffee buyers as a reliable supplier, which contributed for the company to continue their activity in being a model of excellence that generated value to their owners and collaborators.